Trans-Cultural Leadership for Change - Derungs-Ruhier, Isabelle M. (Revue internationale Animation, territoires et pratiques socioculturelles / International Journal of Sociocultural community development and practices / Revista internacional Animación, territorios y prácticas socioculturales)

(untitled) (Département de communication sociale et publique, Université du Québec à Montréal, 2010)
Leaders nowadays are under pressure to adjust their strategies and management styles. Conventional adaptation to their community’s requirement is not enough. Leaders have to rethink their organizational structure and the related strategy to go beyond uncomfortable situations of unpredictable ambiguities and conflicts. The article introduces a concept of leadership for transformation and draft the response to the question: “Could trans-cultural leadership be a “new” approach to preparing and guiding people through organizational changes and developments at a time of global diversification and greater mobility?”